Introduction to Indonesian Culture to Instill Love for the Homeland in Students of Gombak Utara Guidance Center - Abu Halim Kopong; Dzaky Makarim; Devan Putra Sadana; Arie Anang Setyo; Duwi Saputro (International Conference on Education for All, 2023)
North Gombak Guidance Center (SB Gombak Utara) is a place of learning for Indonesian immigrant children or those of Indonesian descent who do not have citizenship documents in Malaysia. Students at this guidance center are not familiar with their parents' cultural background specifically. However, it is important to instill a love for their homeland through cultural exposure to make them dignified Indonesian citizens. The Community Service Program for Education and Culture (KKN-KI) is carried out for 1-2 hours of effective learning per week, involving active participation from students in grades 1, 2, 3, 4, and 5 of elementary school. The program includes: 1) Introduction to the Lompat Gaba dance, 2) Introduction to Indonesian cultural diversity (playing picture matching games), 3) Introduction to the Lalayon dance, 4) Creating designs of typical Indonesian batik, and 5) Introduction to the diversity of Indonesian culture using digital media. Based on the activities conducted, it is found that students have a great interest in getting to know Indonesian culture, but they tend to be hesitant, shy, and distracted when starting. The cultural introduction successfully captivated students and made them understand the culture they inherently possess. This description indicates that similar activities are needed with additional programs and the use of various media. If implemented, students will become much more acquainted with the cultural diversity present. This way, the shared hope of preserving culture and instilling students' interest in returning to their homeland, Indonesia, can be realized.